Physicochemical changes in phosphorylase kinase associated with its activation - Liu, Weiya (Cold Spring Harbor Laboratory Press, 2008)
Phosphorylase kinase (PhK) regulates glycogenolysis through its Ca(2+)-dependent phosphorylation and activation of glycogen phosphorylase. The activity of PhK increases dramatically as the pH is raised from 6.8 to 8.2 (denoted as ↑pH), but Ca(2+) dependence is retained. Little is known about the structural changes associated with PhK's activation by ↑pH and Ca(2+), but activation by both mechanisms is mediated through regulatory subunits of the (αβγδ)(4) PhK complex. In this study, changes in the structure of PhK induced by ↑pH and Ca(2+) were investigated using second derivative UV absorption, synchronous fluorescence, circular dichroism spectroscopy, and zeta potential analyses. The joint effects of Ca(2+) and ↑pH on the physicochemical properties of PhK were found to be interdependent, with their effects showing a strong inflection point at pH ∼7.6. Comparing the properties of the conformers of PhK present under the condition where it would be least active (pH 6.8 − Ca(2+)) versus that where it would be most active (pH 8.2 + Ca(2+)), the joint activation by ↑pH and Ca(2+) is characterized by a relatively large increase in the content of sheet structure, a decrease in interactions between helix and sheet structures, and a dramatically less negative electrostatic surface charge. A model is presented that accounts for the interdependent activating effects of ↑pH and Ca(2+) in terms of the overall physicochemical properties of the four PhK conformers described herein, and published data corroborating the transitions between these conformers are tabulated.